Genes differentially expressed by Mycobacterium tuberculosis after exposure to ruthenium phosphinic compound and isoniazid - Leite, G. G. S.; Baeza, L. C.; Batista, A. A.; Barbosa, M. I. F.; Pavan, Fernando Rogério [UNESP]; Leite, C. Q. F.; Silva, J. L.; Hirata, R. D. C.; Hirata, M. H.; Cardoso, Rosilene Fressati (Bioinfo Publications, 2013)
Background- The evaluation of the effects of new compounds and nonconventional anti-tuberculous drugs have grown and become increas-ingly more popular in recent years. Studies have shown anti-tuberculous activity for Ruthenium complexes, including organometallic com-pounds containing phosphine ligands such as picolinic acid generating great expectations and hopes. Methods- The Representational Difference Analysis (RDA) was applied in order to gain insight about differences in expression of Mycobacte-rium tuberculosis H37Rv exposed to [Ru(dppb)(pic)(bypy)] PF6 (SCAR1) and isoniazid (INH). Total RNA was extracted from the bacillus not exposed and exposed to SCAR1 and INH separately at concentration of MIC for 12 hours at 35Â°C. RDA was carried out and differentially expressed products were sequenced. Results- RDA-sequencing identified, for both compounds, orthologs that encode hypothetical and predict proteins. One related cell wall syn-thesis gene, identified by RDA, and genes related to INH target as inhA, katG and ahpC had their expression confirmed and quantified by real-time PCR. The gene encoding the cell wall associated hydrolase was induced 4.627 and 1.189, inhA 0.983 and 1.027, katG 1.111 and 1.345 and ahpC 1.063 and 1.039 fold after exposure to SCAR1 and INH respectively, compared to not exposed growth. Conclusion- The RDA brings, for the first time, directions to study related genes with metabolic pathways of SCAR1. RDA and Real-Time PCR highlight the idea that one of the SCAR1 interaction, in M tuberculosis may be in the cell wall biosynthesis considering the differential expression of a cell wall hydrolase and warrants further investigation.
Keywords: Mycobacterium tuberculosis; Isoniazid; Ruthenium; cDNA-RDA